Loss of receptor interacting protein kinases 3 and caspase‐8 augments intrinsic apoptosis in tubular epithelial cell and promote kidney ischaemia‐reperfusion injury. Issue 6 (29th April 2019) - Sung, Baekjun; Su, Ye; Jiang, Jifu; Mcleod, Patrick; Liu, Weihua; Haig, Aaron; Green, Douglas R; Zhang, Zhu‐Xu; Jevnikar, Anthony M
ABSTRACT: Background: Ischaemia‐reperfusion injury (IRI) is associated with programmed cell death that promotes inflammation and organ dysfunction. Necroptosis is mediated by members of receptor interacting protein kinases (RIPK1/3). Inhibition of RIPK1/3 provides a pro‐survival benefit in kidney IRI. Caspase‐8 initiates apoptosis and contributes to IRI. We studied whether inhibiting both RIPK3 and caspase‐8 would provide an additional benefit in kidney IRI. Methods: A clamp was applied to the left kidney pedicle for 45 min followed by right kidney nephrectomy. Kidney and serum from wild type, RIPK3 −/−, and RIPK3 −/− caspase‐8 −/− double knockout (DKO) mice were collected post‐IRI for assessment of injury. Tubular epithelial cells (TEC) isolated from wild type, RIPK3 −/−, and DKO mice were treated with interferons‐γ and interleukin‐1β to induce apoptotic death. Results: Kidney IRI of DKO mice did not show improvement over RIPK3 −/− mice. We have found that DKO triggered 'intrinsic' apoptosis in TEC in response to interleukin‐1β and interferons‐γ. Up‐regulation of the B‐cell lymphoma 2 (Bcl‐2)‐associated death promoter, the Bcl‐2‐homologous antagonist killer and Bcl‐2‐associated X protein and enhanced activation of caspase‐3 and 9 were found in DKO TEC. TEC infected with Murine cytomegalovirus that encodes multiple cell death inhibitors resist to death. Conclusion: We show that the deletion of both RIPK3 and caspase‐8 does not provide additive benefit in IRI or TEC death and may enhance injury by up‐regulation of intrinsic apoptosis. This suggests blocking multiple death pathways may be required for the prevention of kidney IRI clinically. Summary at a Glance: Cell death is a feature of renal ischaemia/reperfusion injury and reducing necroptosis by targeting receptor interacting protein kinases (RIPK1/3) has been shown to exert a pro‐survival benefit. In this study, it was investigated whether loss of both RIPK1/3 and the apoptotic mediator caspase‐8 would provide an even greater survival advantage after ischaemia/reperfusion injury. Interestingly, additive benefits were not seen, instead renal injury appeared to be enhanced.